2011
DOI: 10.1177/0009922811410970
|View full text |Cite
|
Sign up to set email alerts
|

Physician Concussion Knowledge and the Effect of Mailing the CDC’s “Heads Up” Toolkit

Abstract: Mailing the CDC's "Heads Up" toolkit appears to affect physicians' recommendations regarding returning to play after a concussion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(52 citation statements)
references
References 14 publications
(19 reference statements)
4
46
0
Order By: Relevance
“…31,40 Given the different state scope of practice laws, there may be a void of availability of TBI continuing education for the chiropractor. The aforementioned findings raise concern over the carry forward of sufficient information and the clinical implementation of the knowledge of brain injuries in relation to both diagnosis and treatment for MTBIs for first-contact MDs 32 and DCs. A literature search reveals a lack of studies on the knowledge transfer of concussion information in practicing DCs, making this a unique population for investigation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…31,40 Given the different state scope of practice laws, there may be a void of availability of TBI continuing education for the chiropractor. The aforementioned findings raise concern over the carry forward of sufficient information and the clinical implementation of the knowledge of brain injuries in relation to both diagnosis and treatment for MTBIs for first-contact MDs 32 and DCs. A literature search reveals a lack of studies on the knowledge transfer of concussion information in practicing DCs, making this a unique population for investigation.…”
Section: Discussionmentioning
confidence: 99%
“…26,[32][33][34][35][36] Specific questions were devised to provide insight into the baseline MTBI knowledge and clinical process of first-contact chiropractic and medical physicians in their evaluation and care of TBI patients. The questions were devised to reflect current concepts, guidelines, and clinical practice.…”
Section: Instrument Developmentmentioning
confidence: 99%
“…Interventions focusing on improving self-efficacy among physicians, such as educational toolkits, formal clinical training, and increased availability of educational resources have been successful in increasing confidence and knowledge among physicians across the board. [31][32][33] As most physicians felt comfortable caring for children with SCD, these educational interventions might be best focused on increasing physician knowledge of the risks and benefits of TCD screening and blood transfusions, as these were areas in need of improvement among all physicians. These educational targets are in line with the SCD-related research agenda released by the NHLBI which identified clear, evidence based guidelines for physicians as a priority, 34 and numerous quality improvement collaborations focused on improving care and outcomes among children with SCD.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to these documents, agencies have developed educational information specific to coaches, athletes, and parents that has been shown to effectively educate the target audience. [54][55][56] Athletes themselves have demonstrated limited knowledge regarding concussion symptoms; more than 50% of high school athletes 57 and 70% of collegiate athletes 58 did not report concussions sustained during football. One reason for nonreporting was that athletes were not aware of the signs and symptoms of concussion.…”
Section: Documentation and Legal Aspectsmentioning
confidence: 99%